ANALISIS SETTING RELAI ARUS LEBIH DAN RELAI GANGGUAN TANAH PADA PENYULANG ABIMANYU 22 kV PADA GARDU INDUK CAWANG - Wisam Abyadha Ibrahim; Teguh Utomo; Mahfudz Shidiq (Jurnal Mahasiswa TEUB, 2023)
At the Cawang Substation there are 3 types of transformers and has several feeders, one of which is the Abimanyu feeder. According to the data that we obtained, the feeder disturbance data in 2020 at the Abimanyu 22 kV feeder experienced 3 trip.In the Abhimanyu feeder, a good relay setting is needed to protect the electrical equipment contained in the feeder and otherelectrical equipment from short circuit fault and overload disturbances. Therefore, a protection system is needed which metthe requirements of sensitivity, reliability, selectivity, and speed is needed to localize the interference. All of these requirementsdepend on the accuracy of the protection equipment used in the distribution channel. The types of protection on distributionlines are overcurrent relays and ground fault relays. Therefore, there is a need for coordination between the supportingcomponents of the protection system, which consists of an Over Current Relay and a Ground Fault Relay on the Abimanyufeeder line. This coordination is intended so that when one of the busbars is disturbed or there is no safety guard that securesthe busbar it will result in an imbalance that will detected by the system and can result in the continuity of the power flow beingdisrupted. In the discussion of this writing, it aims to calculate the magnitude of the short circuit fault current that may occurin the feeder distribution of 22 kV, then determine the settings for the overcurrent relay and ground fault relay on the feeder,then simulate the system using the ETAP program 12.6 based on the results of calculations and data obtained in the field, andexamines the results of ETAP 12.6 calculations and simulations based on the settings of the Over Current Relay and GroundFault Relay on the real condition. The results of this paper can be used as a reference in making coordination of over currentrelay protection and ground fault relay at PT. PLN (Persero) UIT JBB UPT Cawang. Keywords — Relay, Over Current Relay, Ground Fault Relay, Short Circuit, Abimanyu Feeder, ETAP 12.6.0. DAFTAR PUSTAKA[1] A. Gaffar, A. Agussalim, and D. Arisandi, “Analisis Gangguan Hubung Singkat Pada Jaringan Distribusi 20 Kv Di Gardu Induk Panakkukang,” J. Teknol. Elekterika, vol. 1, no. 2, p. 156, 2022.[2] PT. PLN (Persero) Penyaluran dan Pusat Pengatur Beban Jawa-Bali, “Pedoman dan Petunjuk Sistem Proteksi Transmisi dan Gardu Induk Jawa Bali,” PT PLN, no. September, p. 513, 2013.[3] J. Kennedy and R. Eberhart, “Particle Swarm Optimization,” Ind. Electron. Handb. - Five Vol. Set, pp. 1942–1948, 1995.[4] I. Robandi, Artificial Intellegence “Mengupas Rekayasa Kecerdasan Tiruan.” Yogyakarta: ANDI, 2019.[5] H. R. Baghaee, M. Mirsalim, G. B. Gharehpetian, and H. A. Talebi, “MOPSO/FDMT-based Pareto-optimal solution for coordination of overcurrent relays in interconnected networks and multi-DER microgrids,” IET Gener. Transm. Distrib., vol. 12, no. 12, pp. 2871–2886, 2018.[6] Perusahaan Umum Listrik Negara, “SPLN 64 : 1985,” Dep. Pertamb. dan Energi, vol. No.172/DIR, p. 64, 1985.[7] PT.PLN(Persero), “Buku Pedoman Proteksi dan Kontrol Penghantar,” Prot. dan Kontrol Penghantar, p. 7, 2014.1942–1948, 1995.